Nucleus incertus provides eye velocity and position signals to the vestibulo-ocular cerebellum: a new perspective of the brainstem–cerebellum–hippocampus network - Cheron, Guy; Ris, Laurence; Cebolla, Ana Maria (Frontiers in Systems Neuroscience, 2023)
The network formed by the brainstem, cerebellum, and hippocampus occupies a central position to achieve navigation. Multiple physiological functions are implicated in this complex behavior. Among which, control of the eye-head and body movements is crucial. The gaze-holding system realized by the brainstem oculomotor neural integrator (ONI) situated in the nucleus prepositus hypoglossi and fine-tuned by the contribution of different regions of the cerebellum assumes the stability of the image on the fovea. This function helps in recognition of environmental targets and to define appropriate navigational pathways further elaborated by the entorhinal cortex and hippocampus. In this context, an enigmatic brainstem area situated in front of the ONI, the nucleus incertus (NIC), is implicated in the dynamics of brainstem-hippocampus theta oscillation and contains group of neurons projecting to the cerebellum. These neurons are characterized by burst tonic behavior similar to the burst tonic neurons in the ONI that convey eye velocity-position signals to the cerebellar flocculus. Faced with these forgotten cerebellar projections of the NIC, the present perspective discusses the possibility that, in addition to the already described pathways linking the cerebellum and the hippocampus via the medial septum, these NIC signals related to the vestibulo-ocular reflex and gaze-holding could participate in the hippocampal control of navigation